Una vita contro. Conversazione con Lucia Pizzo Russo - Tiziana Andina; Carmelo Calì (Rivista di Estetica, 2011)
The research Lucia Pizzo Russo carried out all over her academic and scientific career is focussed on a the following idea: human mind and behaviour make up a cognitive device from whose complexity stems an evolutionary advantage. Hence, the psychological study of mind should take into account all those cognitive functions that underlie man’s ability of perceiving structures and affordances in the visual world as much as of solving problems, where perception and thought deeply interact, and of giving shape to representations, be they artistic forms or scientific theories. But for an adequate psychological account to obtain that complexity must be traded off against the assumption that mind and behaviour are a psychophysical unity. That means that cognition does imply a neurobiological basis, and at the same time that a phenomenological stance is required just as that instanced by Gestalt psychology. In this interview a picture of a piece of life is meant to be given as it goes along with a research whose reference are issues in psychology, psychology of arts and such figures as Brandi, Piaget, Gombrich, Arnheim, Bozzi.